Kata Mau`izhah dalam Al-Qur’an dalam Kaitannya dengan Ilmu Konseling - Al Ikhlas (Universitas Negeri Padang, 2021)
The pressures of life that continue to increase during the Covid-19 pandemic have made people stressed in living their lives. Therefore, to ease the burden of life so as not to be stressed, advice is needed to deal with a lot of problems properly and to run life normally. For a Muslim, the source of advice in life is the Qur'an. As the word of Allah SWT which was revealed to the Prophet Muhammad to be used as a life guide for humans, it contains various values that can be used as lessons in life. To understand the values, the author researched the words mau'izhah in the Qur'an and its relation to counseling science. This study aims to find out the explanation of the Qur'an about Mau'izah and its relation to advice in counseling science. The method used in this study is library research. The results of this research showed that the word mau`izhah in the Al-Qur'an has several meanings, namely: religious law, warning, and advice. The last meaning is closely related to counseling science.